Citizens’ Readiness to Use Electronic Voting System in Oyo State, Nigeria - Omotayo, Funmilola O.; Adekunle, Olasubomi A. (Asian Journal of Electrical Sciences, 2020)
The right to vote, which is identified as one of the fundamental human rights, encourages civic consciousness through political participation. Elections in Nigeria have been found to record low turnout, which has been partly attributed to problems identified with the traditional voting system used in the county. This study investigated the perception of Oyo state citizens about e-voting system, as well as their readiness to use the system. Descriptive survey research design was adopted. Questionnaire data was collected from 390 respondents, while 20 respondents were also interviewed. Questionnaire data were analysed using the Statistical Package for Social Sciences and presented using descriptive statistics in form of frequency, percentage, mean and standard deviation. The interview data was analysed using Nvivo software, version 10. Findings reveal that citizens perceived the current voting system as stressful and not transparent, and that e-voting system would be better than the present voting system because of the advantages associated with technology use. The citizens are ready to use e-voting system, if adopted by Nigerian government. The study recommends that Nigerian government could adopt and implement e-voting system to reduce the huge financial expenses associated with conduct of elections, as well as some other challenges that have been associated with elections in Nigeria.